RAY-BINNING ANGLE STACK DOMAIN IN ENHANCING THE ROBUSTNESS OF CONVERTED-WAVE SEISMIC JOINT INVERSION - Wahyu Triyoso; Madaniya Oktariena; Lucky Kriski Muhtar (Scientific Contributions Oil and Gas, 2018)
Converted-Wave Seismic has been proven as imaging alternative in aiding conventional seismic data when passing through gas cloud accumulation. However, asymmetrical approximation effect during Converted-Wave Seismic binning still remains in offset domain. PS-Reflection events in offset-domain are mapped using common-ray re-sorting technique by implementing the basic Snell’s Law of Mode Conversion. This produces an Angle Profile correspondent with the PP incident angle. Re-sorting the angle of converted-wave ray path to the PP-Wave propagation within the common imaging point, the Converted-Wave seismic would share similar angle range. Thus, improving the match in PP to PS event as data input preparation for Joint Inversion. Grouping the angle based on AVA Analysis, followed by stacking the Angle Profile into Common-Ray Partial Angle Stack, had proven to eliminate the fault shadow sagging zone and gas absorption illumination area in Converted-Wave Seismic. The final result of PP-Seismic imaging is more coherent with the Converted-Wave Seismic, in term of event alignment and amplitude character. This result lead to more robust PP-PS Joint Inversion, as the coherency between input data is an important key in simultaneous process. The comparison on derived Vp/Vs shows better improvements of subsurface imaging, especially in the near-surface gas masking area of conventional seismic.